Determination of selected heavy metal in road dust along Gambang-Kuatan road - Abu Bakar, Zulkiflli (2012)
Some heavy metals help important role in our body but it also can be a dangerous treat if it been taken for too much. The uncontrolled emission of heavy metal that been discharge by human activities can be transported by water, air and deposited to land surface as road dust. Due to we use road almost every day in purpose go to work or any event, the increases of heavy metal concentration in road dust are might affect human health through inhalation. Since 2009 there is much development and construction activities actively grow in kuantan, especially in Kuantan - Gambang road including industrial and residential area. Review from literature showed that heavy metal concentrations are greater at area closer to industrial and construction activities. It also shows that communities who live near highway might be having higher asthma and allergy rate. The objective of this study is to determine the concentration of heavy metal in road dust of Kuantan - Gambang road. Road dust samples were collected from several sites covering residential area, industrial area, airport, campus UMIP, bus terminal and agriculture area. Heavy metals, including Cr (chromium), Mn (manganese), Fe (ferum), Ni (nickel), Zn (zinc), Pb (plumbum), Cu (cuprum) and Cd (cadmium) have been selected in this study. After sampling, the samples were heated in muffle furnace up to 550°C for 4 hours to remove any possible organic matter. After that, the samples were digested using aqua regia and were determined by using atomic absorption spectrometer (AAS). Results showed that heavy metals concentration in road dust samples were ranged from 0.01 tg/g to 60.00 .tg/g. Sampling site with the highest concentration of heavy metals was the road that far from Kuantan. Meanwhile, for site that contain lowest concentration of heavy metals was the mining area at Gambang which located far away from Kuantan. In addition, cadmium and chromium were below the detection limit.